Green IT based energy efficiency model for data centers to reduce energy consumption & CO2 emissions - Uddin, Mueen; Abdul Rahman, Azizah; Shah, Asadullah (Radiance Bahu - Uddeshiya Sanstha, 2011)
Problem Statement: The advancement of Information and Communication Technologies (ICTs) based business and social practices in the last few decades has transformed many, if not most, economies into e-economy and businesses into e-businesses. For economies, ICTs are increasingly playing critical roles in transforming and generating ortunities. On the other hand, global warming and climate change coalescing with limited availability and rising cost of energy are posing serious challenges for the sustainability of the global digital (or otherwise) economy. Technology has a potential to create sustainable business and society both in grim and green economic times. Especially, the recovery from the current economic crisis is going to need and lead to more Greener and energy efficient industries. As corporations look to become more energy efficient, they are examining their operations more closely. Data centers provide capabilities of central storage, backups and networking, recovery. Data centers are found major culprits in consuming too much energy in their overall operations and generating too much CO2. In order to handle the sheer magnitude of today’s data, data centers have had to use much more power and servers have become larger, denser, hotter and significantly more costly to operate. This study determine the properties and attributes of green IT infrastructures and determines the way it will be helpful in achieving green sustainable businesses. The proposed Green IT model will be drafted using Virtualization technology for data centers to make them more energy efficient and green, hence reducing the emission of green house gases so that the overall effect on global warming can be reduced or even eliminated. Results & Conclusion: The proposed model would reveal the qualities of green IT to enhance the proper utilization of hardware and software resources available in the data center. It helps data center managers to come up with a new environment friendly and sustainable green IT strategy making environment greener and sustainable. The heart of this strategy is to reduce global warming effects by using green and energy efficient data centers.